Coffee Agroindustry in South Konawe Regency, Southeast Sulawesi Province, Indonesia: A case study - Rianse, Ilma Sarimustaqiyma; Rianse, Muhammad Iqbal Kusumabaka; Awaluddin, Andi; Sudarmo, Hadi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
The purpose of this research is to find out and describe the feasibility of coffee farming at the level of farmers who cultivate coffee beans and at the level of home industries in South Konawe Regency which produce packaged ground coffee or known as the brand name (Anoa Coffee). The parameters used to assess the financial feasibility of coffee farming are by calculating the value of R/C, NPV and NBCR at interest rates of 12% and 35% of farming and coffee powder processing businesses. Based on the R/C ratio, a value of 16 is obtained, this shows the benefits of coffee farming, where every IDR 1,000,000 invested in coffee farming will generate 16 times the income. The NPV value of coffee farming has a value of IDR 36,141,085, supported by an NBCR value of 2.04, and the ground coffee processing business by CV. Kopindo Sukses Bersama obtained an NPV value of IDR 10,153,539,739, and also an NBCR value of 2.05, meaning that smallholder coffee farming in South Konawe Regency is financially profitable and feasible to develop.